Cartoon is not a synonym for children´s program (Journal of Parents and Teachers, 2014)
From the early childhood, kids are attracted to television, and parents allow them to watch their favourite cartoons. However, neither the fact that the characters are drawings, nor the fact that the program is issued during TV children´s schedule, indicate the content is appropriate for kids. Therefore, it is important children watch television with adults and during the shortest possible time. Finally, two films are proposed to work in the classroom.
Keywords: Cartoons; television; television consumption; inappropriate content.